Effects of a protocol with manual therapy and postural techniques for non-specific low back pain - Silva, Daniele Alves da; Carvalho, Maria Ester Ibiapina Mendes de; Mesquita, Laiana Sepúlveda de Andrade (Manual Therapy, Posturology & Rehabilitation Journal, 2019)
Background: The effects of postural reeducation on low back pain (LBP) are well documented in the literature, as well as studies using manual therapy (MT). However, no studies were found that investigate the use of a protocol using both MT and postural techniques. Objective: To verify the effects of a protocol that associates the MT and postural techniques in pain symptoms and functionality of subjects with chronic non-specific LBP. Methods: The participants of this study were 09 patients from the physiotherapy outpatient clinic of a public hospital. The evaluation of the subjects was carried out with the application of the Visual Analog Scale for Pain, Oswestry Disability Index (ODI) and Pressure Algometry. Patients were treated with a protocol composed of manipulative and postural techniques performed twice a week for five weeks. Two new evaluations were performed after the 5th and 10th sessions. For statistical analysis, the ANOVA test was used followed by the Tukey post-hoc test, considering p< 0.05. Results: In all the evaluated variables it was observed a greater difference of the scores between the initial and the tenth evaluation. There was significant improvement in the pain (p = 0.0167) and in the algometry of the piriformis and quadratus lumborum. There was no significant difference in disability (p = 0.0595). Conclusion: The protocol with MT and postural techniques promoted improvement of pain and increase of pressure sensitivity threshold in patients with chronic non-specific LBP.